Editorial: Decision-Making in Youth Sport - Silva, Ana Filipa (2021)
Understanding decision-making in team sports motivated us to propose a Frontiers topic with eight published articles. These present different approaches to decision-making research in sports, partially confirming the hidden variation of experimental approaches related to this topic. Decision-making is a complex process that plays a determinant role in sports performance. Knowledge related to the quality and effectiveness of this process is still being acquired, both in research and in practice. This may justify the fact that many studies are still focused on describing the decisions made, which more than bridge the gap for practice and with training interventions for developing children and young athletes. Possibly, further interventions should be made in the future. Expecting to welcome different approaches to decision-making in youth sports, we aimed to improve the science and the practice in this specific field. Some of the included articles were descriptive, others proposed new approaches for training, and some synthesized the available evidence about training interventions.